2013
DOI: 10.1371/journal.pone.0074936
|View full text |Cite
|
Sign up to set email alerts
|

Actin Structure-Dependent Stepping of Myosin 5a and 10 during Processive Movement

Abstract: How myosin 10, an unconventional myosin, walks processively along actin is still controversial. Here, we used single molecule fluorescence techniques, TIRF and FIONA, to study the motility and the stepping mechanism of dimerized myosin 10 heavy-meromyosin-like fragment on both single actin filaments and two-dimensional F-actin rafts cross-linked by fascin or α-actinin. As a control, we also tracked and analyzed the stepping behavior of the well characterized processive motor myosin 5a. We have shown that myosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 52 publications
(95 reference statements)
5
26
1
Order By: Relevance
“…We found little evidence of processive movements when probing M10HMM in the optical trap under our usual protocol, which uses a trap stiffness of ∼0.03 pN/nm. However, on lowering the trap stiffness, short processive runs could then be seen, showing both forward and backward steps of ∼35 nm, similar to the center of mass translocation value obtained via single molecule TIRF imaging assays [∼34 (18) and ∼31 nm (19)], but significantly longer than values obtained by Nagy et al (15) and Ricca and Rock (17), who found steps of 18 nm on F-actin bundles and a mixture of 10-to 20-nm steps on single surface-immobilized F-actin filaments. Nagy and Rock (16) also carried out optical tweezers experiments using F-actin bundles and found a load-dependent step size that was 18 nm at higher loads and 12 nm at lower loads.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We found little evidence of processive movements when probing M10HMM in the optical trap under our usual protocol, which uses a trap stiffness of ∼0.03 pN/nm. However, on lowering the trap stiffness, short processive runs could then be seen, showing both forward and backward steps of ∼35 nm, similar to the center of mass translocation value obtained via single molecule TIRF imaging assays [∼34 (18) and ∼31 nm (19)], but significantly longer than values obtained by Nagy et al (15) and Ricca and Rock (17), who found steps of 18 nm on F-actin bundles and a mixture of 10-to 20-nm steps on single surface-immobilized F-actin filaments. Nagy and Rock (16) also carried out optical tweezers experiments using F-actin bundles and found a load-dependent step size that was 18 nm at higher loads and 12 nm at lower loads.…”
Section: Discussionsupporting
confidence: 68%
“…Notably, the chimeric myosin-5a/SAH HMM construct used by Baboolal et al (23) also released ADP in a monoexponential manner. Because both the myosin-5a/SAH-containing HMM (23) and M10HMM (15,(17)(18)(19) constructs exhibit processive motion at low load, we conclude that strong kinetic gating of ADP release is not a prerequisite for processivity (23).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The results show that myosin 6 moves along actin with a much more variable step size and that myosin 7a takes somewhat shorter steps than myosin 5a. FIONA measurements of myosin 10 are somewhat controversial with a range of values reported [7577]. The longer step size of 36 nm is surprisingly similar in magnitude to that of myosin 5a as the lever arm of myosin 10 binds only three calmodulins.…”
Section: 6 Super-resolution Tracking Of Moving Myosinsmentioning
confidence: 99%
“…Actin filament assembly and bundling can also be mediated by the combined properties of Enabled (Ena, a member of the Ena/vasodilator-stimulated phosphoprotein family) and fascin-1 [20]. Once assembled, fascin-1/Factin bundles provide surfaces for the motion of myosin motors that promote specific motion and stepping characteristics [21][22][23]. This property may be important for cargo transport dynamics within filopodia [24].…”
Section: Fascin-1: Molecular Functionsmentioning
confidence: 99%